Avatar, the last airbender. North and south. Part two - Yang, Gene Luen (Dark Horse Books, 2017)
After trying to kidnap Katara and Sokka, Gilak disappears, leaving only a haunting note. And when Gilak's crew strikes again, troubling information is revealed, and Katara's worst fears may be confirmed.